PROFIL WIRAUSAHA KULINER DI PEKANBARU TAHUN 2020 - Sukarni Sukarni (Universitas Sebelas Maret, 2020)
This research was conducted to answer the problem (1) How to describe the level of education and sales turnover of entrepreneurs in Pekanbaru, (2) How to describe the benefits and types of entrepreneurial business in Pekanbaru, (3) Is there a relationship between profitability and entrepreneurial profile in Pekanbaru. The sample of this study was taken 60 entrepreneurs with pourporsive sampling. Data were analyzed with non-parametric statistics. the results of this study. Knowing the relationship between education level and entrepreneurial sales turnover in Pekanbaru. The level of education correlates with turnover and the number of employees this is indicated by the acquisition value of Sign <0.05, while the type of business, the level of education does not correlate with earnings, gender and length of business due to the acquisition of Sign value> 0.05. Profit correlates significantly with turnover and length of business, this is indicated by the Sig value obtained <0.05. While profits are not related to the type of business, education level, gender and number of employees, this can be seen from the Sig value obtained> 0.05. The type of business is positively correlated with turnover, gender and number of employees, this can be seen from the acquisition of sign <0.05, while the type of business has no relationship with earnings, education level, duration of business because the sign value> 0.05.Key words: culinary, entrepreneurship, profile, profit, turnover